Occupational Radiation Exposure of Anesthesia Providers: A Summary of Key Learning Points and Resident-Led Radiation Safety Projects. (June 2017) - Wang, Rachel R.; Kumar, Amanda H.; Tanaka, Pedro; Macario, Alex
Anesthesia providers are frequently exposed to radiation during routine patient care in the operating room and remote anesthetizing locations. Eighty-two percent of anesthesiology residents (n = 57 responders) at our institution had a "high" or "very high" concern about the level of ionizing radiation exposure, and 94% indicated interest in educational materials about radiation safety. This article highlights key learning points related to basic physical principles, effects of ionizing radiation, radiation exposure measurement, occupational dose limits, considerations during pregnancy, sources of exposure, factors affecting occupational exposure such as positioning and shielding, and monitoring. The principle source of exposure is through scattered radiation as opposed to direct exposure from the X-ray beam, with the patient serving as the primary source of scatter. As a result, maximizing the distance between the provider and the patient is of great importance to minimize occupational exposure. Our dosimeter monitoring project found that anesthesiology residents (n = 41) had low overall mean measured occupational radiation exposure. The highest deep dose equivalent value for a resident was 0.50 mSv over a 3-month period, less than 10% of the International Commission on Radiological Protection occupational limit, with the eye dose equivalent being 0.52 mSv, approximately 4% of the International Commission on Radiological Protection recommended limit. Continued education and awareness of the risks of ionizing radiation and protective strategies will reduce exposure and potential for associated sequelae.